Evaluation of multimodal imaging guided multifunctional bio-targeted reactive oxygen species production synergists: a preliminary study - Ou, Xia; Tang, Yu; Yang, Haiyan; Du, Yan; Zhang, Zhong; Lin, Li; Wang, Qi; Zou, Jianzhong (Frontiers in Materials, 2025)
ObjectivePulse focused ultrasound (PFUS) is facing the big challenge of rapid attenuation of ultrasonic energy. Although synergists existed are helpful, they have limitations such as poor targeting, incomplete imaging during therapy, and tumor residue after therapy. This study aims to construct bio-targeted reactive oxygen species (ROS)- producing synergists (abbreviated as B.bifidum@PC-CLs) consisting of Bifidobacterium bifidum (B. bifidum) and multifunctional ROS producing nanoparticles (abbreviated as PC-CLs) loaded with chlorin e6 (Ce6) a multifunctional nd perfuorohexane (PFH), which is expected to make up for the shortcomings of existing PFUS collaborative therapy, and provide an idea for tumor diagnosis and treatment.MethodsThe PC-CLs were prepared for testing the capability of multimodal imaging, ROS production and SDT intracellular, and synergistic effect in vitro. The tumor-targeted ability of B.bifidum@PC-CLs was detected through electrostatic adsorption. The synergistic therapy and antitumor therapy of B.bifidum@PC-CLs with PFUS were analyzed in vivo.MethodsStudies validated that PC-CLs have excellent abilities of multimodal imaging, ROS-producing and SDT-enhancing. Moreover, B.bifidum could not only actively target 4T1 tumor and prolify itself, but also facilitate the delivery and retain of PC-CLs in tumor during electrostatic adsorption. Importantly, B.bifidum@PC-CLs amplified cavitation effect and PFUS-SDT combined antitumor effect.ConclusionA multifunctional bio-targeted B.bifidum@PC-CLs was constructed successful, which may provide an unique nanoparticle platform to guide PFUS for efficient and safety tumor treatment.